Case report on management of Adenomyosis with Ayurveda - Sangwan, Pratibha; sangwan, Sushila (International Research Journal of Ayurveda & Yoga, 2021)
Adenomyosis is a very common condition of invasion of endometrium into the myometrium with endometrial glands and stroma. It is commonly presented with a benign growth and uterus is enlarged. The patient presents with the symptoms like pain (may be chronic or acute) associated with menstruation and variable bleeding pattern. It is a great challenge to treat adenomyosis and hysterectomy has been the only way to treat it. Ayurveda can give a better relief to patient. In this case study, treatment with Kanchnar guggulu, Patrangasav, Ashokaritha and Matra basti has been found useful.